Guilt from Promise-Breaking and Trust in Markets for Expert Services - Theory and Experiment - Adrian Beck; Rudolf Kerschbamer; Jianying Qiu; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2010)
We examine the influence of guilt and trust on the performance of credence goods markets. An expert can make a promise to a consumer first, whereupon the consumer can express her trust by paying an interaction price before the expert's provision and charging decisions. We argue that the expert's promise induces a commitment that triggers guilt if the promise is broken, and guilt is exacerbated by higher interaction prices. An experiment qualitatively confirms our predictions: (1) most experts make the predicted promise; (2) proper promises induce consumer-friendly behavior; and (3) higher interaction prices increase the commitment value of proper promises.
Keywords: C72; C91; D82; 330; Promises; Guilt; Trust; Credence Goods; Experts; Reciprocity; Vertrauensgüter; Sachverständige; Dienstleistungsqualität; Vertrauen; Konsumentenverhalten; Erwartungstheorie; Theorie; Test